Relationship of 25 Hydroxyvitamin D Levels with C-Telopeptide Levels in Perimenopausal Women - T. Sumarlin; Eddy Suparman; Hermie M. M. Tendean (Eduvest - Journal of Universal Studies, 2025)
Osteoporosis represents a significant global health challenge, particularly affecting perimenopausal women who experience accelerated bone loss due to declining estrogen levels. The relationship between vitamin D status and bone turnover markers during this critical transition period requires further investigation to optimize preventive strategies. This study [A1] aims to examine the relationship between 25-Hydroxyvitamin D (25(OH)D) and C-Telopeptide (CTx) levels in perimenopausal women in Manado. Vitamin D has an important role in maintaining bone health, and its deficiency can have an impact on a variety of health problems. This cross-sectional study involved 30 participants from Prof. Dr. R.D. Kandou Hospital and network hospitals in Manado. The results showed that 50% of the respondents had sufficient levels of 25(OH)D, while the remaining 50% were in the deficient category. The average level of 25(OH)D was 30.30 ng/mL. For CTx, 60% of respondents were at high risk and the remaining 40% were at low risk, with an average of 0.67 ng/mL. However, a non-parametric correlation test (Spearman's rho) between 25(OH)D and CTx showed statistically insignificant results (r=0.024; p=0.902). Therefore, this study concluded that there was no statistically significant relationship between 25(OH)D and CTx levels in perimenopausal women in the sample studied.